Fiqh al-Aqalliyy?t - Hassan, S. author. aut Link
XVI, 216 p.
Keywords: This book examines the development of a contemporary internal debate among Muslim minorities living in Western Europe and North America to establish a specific form of Islamic jurisprudence. Fiqh al-aqalliyyat attempts to strike a balance between Muslim's religious commitments and their civic identity as citizens in Western liberal states.